Training of Thesis Conversion into Scientific Articles - Multazam Abubakar; Annisa Shofa Tsuraya; Muthi’ah Muthi’ah; Nur Aliyah Nur; Muhammad Syahruddin Nawir (MITRA: Jurnal Pemberdayaan Masyarakat, 2023)
Final-year students encounter problems in converting their thesis into scientific articles as one of the requirements from the Ministry of Higher Education to graduate from university. This community service aimed at providing insight to final-year students about how to write scientific articles which are composed of their theses, how to use reference managers, such as Mendeley, and how to submit research articles in a scientific journal using OJS. The participants of this activity were the final-year students and fresh graduates of the English Education Department, Tarbiyah dan Teaching Science Faculty, UIN Alauddin Makassar. The method used in this activity was named ’training’ by applying The Training Circle approach. The activity was held in four steps, which were identifying training needs, deciding the aims and planning of training, implementation of training, and evaluation. The result showed that the students understand how to convert their theses into scientific articles, how to use referencing manager and make an account, as well as how to submit their articles in ELTIES journals using OJS.